Classroom management and academic effectiveness: bibliometric review based on the Scopus database - Mercado Hermenegildo, Arturo (2023)
The purpose of this research was to carry out an exhaustive bibliometric review of classroom management related to academic effectiveness, in the Scopus database, for this purpose it was based on a multidisciplinary international bibliographic exploration on the topic in question, the search strategy had the following criteria: Initial search based on the variables “classroom management” and “academic effectiveness” linked with the Boolean operator AND, obtaining 262 results, then the search was limited to the time range from 2011 to 2021, obtaining with This resulted in 156 matches, then it was limited to only scientific articles, that is, conferences, newspapers, etc. were excluded, obtaining 102 articles, then a new filter of only open access documents was applied, which obtained a result final of 36 articles, which were exported to Bibliometrix statistical software, the results provided a broad understanding of the current state of the subject of study, focused on high-quality scientific production and its distribution over 10 years, as well as the evaluation from the most notable authors, sources and countries, which provided a valuable starting point for future researchers, thus contributing to the progress of scientific knowledge regarding classroom management related to academic effectiveness.